Proposal for intervention for the conservation and restoration of the Brum Chapel (Recife/PE) - Amorim , Emanoel Silva de; Lordsleem Jr., Alberto Casado; Menezes , Thiago Araújo de; Sampaio , Girlândia de Morais; Monteiro , Eliana Cristina Barreto (National Journal of City Management, 2024)
This study aims to diagnose the pathological manifestations of the Brum Chapel, using four methodological steps, namely: characterization of the area, diagnosis, damage mapping, and guidelines for the restoration project. The case study was carried out at the Brum Chapel, located in the city of Recife/PE, in the northeast region of Brazil between 2020 and 2021. In this way, the research was able to guarantee the preservation and dissemination of facts and historical achievements of the Brazilian Army (responsible for the property), extolling the participation of the northeastern soldier in all historical episodes in the state of Pernambuco, providing culture and knowledge to visitors, in addition to recognition at the regional level, as a preservation agency and an example of conservation of military-religious architecture from the 17th century. The results obtained demonstrated the natural process of evolution of pathological manifestations, raising awareness of heritage management for planning and carrying out maintenance, enabling the compatibility of the building's needs with the available financial resources. It is concluded that in this process, public policies should make these actions viable through tax incentives that allow for the proper conservation of this property, respecting its original function.
Keywords: Damage mapping; Diagnosis of pathological manifestations; Building inspection